Tanggung Jawab Hukum Inventor Atas Invensi Kecerdasan Buatan (Artificial Intelligence) Di Indonesia - Putranti, Deslaely; Anggraeny, Kurnia Dewi (UI Scholars Hub, 2022)
The pace of technological development can no longer be restrained until the emergence of artificial intelligence (AI) which later, turns out to have a negative impact on its application. AI is a computer system program created by humans. However, the invention of AI in one hand makes human work easier, it is also noticeable that there are several criminal cases